Evaluation of Antioxidant activity, Antimicrobial activity, Anticancer activity and DNA Barcoding of Lepidagathis barberi Gamble - Reshma R.L; Mary Kensa V (The Bioscan, 2026)
The present study investigates the antioxidant, antimicrobial, anticancer potential and molecular identification of whole dried plant powder of Lepidagathis barberi.